John Stith and Mary Randolph Stith papers - Stith, John, -1715.; Stith, Mary Randolph, active 1734.
Transcripts of fragments of the will and deposition of John Stith; and a transcript of the will of Mary Randolph Stith.
Handwritten transcripts.
Virginia militia officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Wills -- Virginia; Militia officers